FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN DENGAN DIVIDEN SEBAGAI MODERASI DI FOOD BEVERAGE - Ayuningrum, Anggrainy Putri; Meliza; Suryadi , Dara Tanesia (Program Studi Akuntansi Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2025)
Food and beverage is one of the companies that is resistant to the crisis so that many investors choose the company in investment. Making investment decisions, investors consider various factors, one of which is the value of the company itself. Fundamental factors that are believed to affect firm value include Investment Opportunity Set, Liquidity, and Leverage. In line with this, this study aims to examine how IOS , Liquidity, and Leverage affect Firm Value in the food and beverage industry sector listed on the Indonesia Stock Exchange (IDX) for the period 2021-2023. In addition, this study also examines the role of dividend policy as a moderating variable in the relationship. The data used is secondary data, with a purposive sampling method that resulted in 24 companies as research samples. The analysis techniques used include multiple linear regression as well as moderation regression analysis (MRA) with the help of SPSS software version 20. Based on the results of the study, it is known that MVBVA has a significant negative effect on PBV. Meanwhile, CR shows a positive influence on PBV, but is not statistically significant. On the other hand, DER exerts a significant positive influence on PBV. This study also found that DPR was able to strengthen the relationship between MVBVA and PBV, but did not manage to moderate the relationship between CR and PBV. In contrast, DPR is effective in strengthening the effect of DER on PBV.